2018
DOI: 10.1016/j.foodres.2018.04.031
|View full text |Cite
|
Sign up to set email alerts
|

The paradoxical effect of extra-virgin olive oil on oxidative phenomena during in vitro co-digestion with meat

Abstract: Extra-virgin olive oil is an integral part of the Mediterranean diet and its consumption has been associated with a reduction risk of chronic diseases. Here we tested the potential of extra-virgin olive oil to limit the oxidative phenomena during in vitro gastro-intestinal co-digestion with turkey breast meat. The extra-virgin olive oil was particularly rich in oleuropein aglycone isomers, which represented the 66.8% of total phenolic determined with MS/MS experiments. Meals supplemented with extra-virgin oliv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
33
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 29 publications
(35 citation statements)
references
References 47 publications
0
33
2
Order By: Relevance
“…Separation was performed with a C18 column (HxSil C18 Reversed phaseHamilton, 250 × 4.6 mm, 5 μm particle size, Hamilton Company, Reno, NV, USA) by using a binary gradient of water/formic acid and acetonitrile. The mobile phase composition, the flow rate, the elution gradient, the negative and positive ESI-MS parameters as well as the quantification method are fully described in Martini et al [ 24 , 29 ] and Mekam et al [ 30 ].…”
Section: Methodsmentioning
confidence: 99%
“…Separation was performed with a C18 column (HxSil C18 Reversed phaseHamilton, 250 × 4.6 mm, 5 μm particle size, Hamilton Company, Reno, NV, USA) by using a binary gradient of water/formic acid and acetonitrile. The mobile phase composition, the flow rate, the elution gradient, the negative and positive ESI-MS parameters as well as the quantification method are fully described in Martini et al [ 24 , 29 ] and Mekam et al [ 30 ].…”
Section: Methodsmentioning
confidence: 99%
“…After cooking, the meat was cooled on ice and stored at −80°C overnight. The frozen meat was then homogenized in a laboratory blender and divided in portions of 5 g [18]. Grilled and homogenized meat was in vitro digested following the protocol previously developed within the COST Action INFOGEST with modifications [16].…”
Section: In Vitro Gastro-intestinal Digestion Of Beef Chicken Pork mentioning
confidence: 99%
“…[1][2][3][4] The oxidation of protein and PUFAs was previously demonstrated during in vitro gastrointestinal digestion of meat, fish (oils), and vegetable oils. [5][6][7][8][9] The majority of studies investigating oxidation during in vitro digestion of DOI: 10.1002/mnfr.201900404 foods, focused on the effect of different heat treatments, [10] different fat sources, [7,11,12] or the effect of various additives such as myoglobin/heme-Fe, [13] antioxidants, [5,9,14] or nitrite-curing and salting, [6,15] within one or a limited amount of muscle food matrices and/or oils. These studies showed that myoglobin/heme-Fe catalyzes oxidation during digestion, and the presence of suitable antioxidants can prevent these reactions.…”
Section: Introductionmentioning
confidence: 99%